2018
DOI: 10.1055/a-0752-4615
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Concentration of Klotho Protein, Osteocalcin, Leptin, Adiponectin, and Bone Mineral Density in Patients with Chronic Kidney Disease

Abstract: Patients with early-stage chronic kidney disease (CKD) are susceptible to changes in metabolic processes. Partial loss of kidney function leads to homoeostatic disturbances in bone and fatty tissue. The aim of this study was to investigate the association between plasma concentrations of Klotho protein, FGF23, leptin, adiponectin, osteocalcin, and bone mineral density (BMD) in patients with CKD in the pre-dialysis period. The study involved 52 patients with CKD and 23 patients with no kidney disease. In both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Metabolites 2020, 10, 98 2 of 11 lipid profile and serum adipokine levels [3][4][5]. Changes in adipokine levels have been discussed in the context of CKD progression and the risk of comorbidities [6][7][8][9]. Leptin is one of the hormones secreted by adipose tissue and has been recognized as a signaling molecule that regulates energy homeostasis [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites 2020, 10, 98 2 of 11 lipid profile and serum adipokine levels [3][4][5]. Changes in adipokine levels have been discussed in the context of CKD progression and the risk of comorbidities [6][7][8][9]. Leptin is one of the hormones secreted by adipose tissue and has been recognized as a signaling molecule that regulates energy homeostasis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This protein also plays an important role in immune regulation and inflammation, both closely associated with oxidative stress and endothelial dysfunction, which may affect the risk of cardiovascular disorders [12][13][14]. Previous studies showed increased concentrations of leptin in the serum of patients with CKD [7,15]; however, the mechanism of this change is not well elucidated. CKD is also associated with significant lipid disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Potential mechanisms of the increased cardiovascular risk in CKD also include changes in the lipid profile and serum adipokine levels. Over the past few years, changes in adipokine levels in the context of CKD progression and the risk of comorbidities have been investigated by many researchers [ 9 , 13 , 14 , 15 , 27 , 76 , 82 , 83 ].…”
Section: Effects Of Increased Leptin Concentrations On the Risk Of Cardiovascular Disease In Patients With Ckdmentioning
confidence: 99%
“…One of the most investigated adipokines is leptin. Circulating leptin levels are elevated even in the early stages of CKD [ 7 ], and leptin levels increase with disease progression [ 15 , 16 ]. A number of studies have shown that leptin is involved in both CKD progression and CKD complications [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is typically elevated in patients with renal failure, whereas deterioration of the renal function leads to homoeostatic disturbances in bone and adipose tissue [16,17]. Although leptin has important roles in bone remodeling, its effect on bone density of patients on hemodialysis is unclear.…”
Section: Introductionmentioning
confidence: 99%